Exploratory social network analysis with Pajek - Nooy, Wouter de, 1962-; Mrvar, Andrej; Batagelj, Vladimir, 1948- (England ; New York : Cambridge University Press, 2011)
"This is the first textbook on social network analysis integrating theory, applications, and professional software for performing network analysis (Pajek). Step by step, the book introduces the main structural concepts and their applications in social research with exercises to test the understanding. In each chapter, each theoretical section is followed by an application section explaining how to perform the network analyses with Pajek software. Pajek software and data sets for all examples are freely available, so the reader can learn network analysis by doing it. In addition, each chapter offers case studies for practicing network analysis. In the end, the reader has the knowledge, skills, and tools to apply social network analysis in all social sciences, ranging from anthropology and sociology to business administration and history"--Provided by publisher.
Machine generated contents note: Part I. Fundamentals: 1. Looking for social structure; 2. Attributes and relations; Part II. Cohesion: 3. Cohesive subgroups; 4. Sentiments and friendship; 5. Affiliations; Part III. Brokerage: 6. Center and periphery; 7. Brokers and bridges; 8. Diffusion; Part IV. Ranking: 9. Prestige; 10. Ranking; 11. Genealogies and citations; Part V. Roles: 12. Blockmodels; 13. Eandom graph models; Appendix 1. Getting started with Pajek; Appendix 2. Exporting visualizations; Appendix 3. Shortcut key combinations.
Includes bibliographical references and indexes.
Keywords: Pajek (Electronic resource); Social networks -- Mathematical models; Social networks -- Computer simulation